2021
DOI: 10.1111/tpj.15465
|View full text |Cite
|
Sign up to set email alerts
|

ERF108 from Poncirus trifoliata (L.) Raf. functions in cold tolerance by modulating raffinose synthesis through transcriptional regulation of PtrRafS

Abstract: Ethylene-responsive factors (ERFs) are plant-specific transcription factors involved in cold stress response, and raffinose is known to accumulate in plants exposed to cold. However, it remains elusive whether ERFs function in cold tolerance by modulating raffinose synthesis. Here, we identified a cold-responsive PtrERF108 from trifoliate orange (Poncirus trifoliata (L.) Raf.), a cold-tolerant plant closely related to citrus. PtrERF108 is localized in the nucleus and has transcriptional activation activity. Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 91 publications
(116 reference statements)
0
39
0
Order By: Relevance
“…Expression of IAA27 and SAUR71 was significantly upregulated in ‘SY’ under cold stress, indicating that they could be used as candidate genes for further research into the mechanism of auxin in regulating grape cold resistance. In recent years, an increasing number of studies have reported the important regulation effect of ERF in the cold resistance of fruit trees [ 41 , 48 , 52 , 53 ]. ERF genes involved in grape cold resistance have also been reported, including VaERF057 [ 54 ] and VaERF092 [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of IAA27 and SAUR71 was significantly upregulated in ‘SY’ under cold stress, indicating that they could be used as candidate genes for further research into the mechanism of auxin in regulating grape cold resistance. In recent years, an increasing number of studies have reported the important regulation effect of ERF in the cold resistance of fruit trees [ 41 , 48 , 52 , 53 ]. ERF genes involved in grape cold resistance have also been reported, including VaERF057 [ 54 ] and VaERF092 [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fine-tuning of ethylene content in tissues affects plant growth and development [ 34 ]. Liu et al [ 35 ] found that ERF9 could be induced by ethylene under low-temperature conditions [ 36 ]. The transmission of the brassinosteroid signal finally makes the transcription factor family BES1/BZR1 accumulate in a non-phosphorylated state, which activates downstream transcriptional regulation in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…: 91‐95‐2, Sigma‐Aldrich, Saint Louis, MO, USA) or nitro blue tetrazolium (NBT; CAS No. : 298‐83‐9, Sigma‐Aldrich, Saint Louis, MO, USA) as previously described (Khan et al., 2021). All measurements were performed with three independent biological replicates.…”
Section: Methodsmentioning
confidence: 99%